Application of ChatGPT as a content generation tool in continuing medical education: acne as a test topic - Luigi Naldi; Vincenzo Bettoli; Eugenio Santoro; Maria Rosa Valetto; Anna Bolzon; Fortunato Cassalia; Simone Cazzaniga; Sergio Cima; Andrea Danese; Silvia Emendi; Monica Ponzano; Nicoletta Scarpa; et al. (PAGEPress Publications, 2024)
The large language model (LLM) ChatGPT can answer open-ended and complex questions, but its accuracy in providing reliable medical information requires a careful assessment. As part of the AICHECK (Artificial Intelligence for CME Health E-learning Contents and Knowledge) Study, aimed at evaluating the potential of ChatGPT in continuous medical education (CME), we compared ChatGPT-generated educational contents to the recommendations of the National Institute for Health and Care Excellence (NICE) guidelines on acne vulgaris. ChatGPT version 4 was exposed to a 23-item questionnaire developed by an experienced dermatologist. A panel of five dermatologists rated the answers positively in terms of "quality" (87.8%), "readability" (94.8%), "accuracy" (75.7%), "thoroughness" (85.2%), and "consistency" with guidelines (76.8%). The references provided by ChatGPT obtained positive ratings for "pertinence" (94.6%), "relevance" (91.2%), and "update" (62.3%). The internal reproducibility was adequate both for answers (93.5%) and references (67.4%). Answers related to issues of uncertainty and/or controversy in the scientific community scored the lowest. This study underscores the need to develop rigorous evaluation criteria for AI-generated medical content and for expert oversight to ensure accuracy and guideline adherence.